Chew and spit (CHSP) in bariatric patients: a case series - Aouad, Phillip (J Eat Disord, 2021)
BACKGROUND: Studies into the disordered eating behaviour of chew and spit have alluded to several cohorts more likely to engage in the behaviour, one such group being bariatric surgery candidates and patients. Weight-loss surgery candidates have received little to no attention regarding engaging in chew and spit behaviour. Changes in pre- and post- surgery eating pathology related to chew and spit behaviour has yet to be explored and described in academic literature. CASE PRESENTATION: The current study reports on three cases of individual women, aged 30, 35, and 62 respectively, who indicated engagement in chew and spit. All three cases underwent bariatric surgery (two underwent gastric bypass, one underwent vertical sleeve gastrectomy). Eating pathology—including chew and spit behaviour, anxiety and depression, and adherence to the Norwegian nutritional guidelines were examined pre-operatively and post-operatively (one and two-year follow-up). At baseline (pre-surgery), two participants reported that they engaged in chew and spit, compared to one patient post-surgery. All three cases reported that they, to at least some extent, adhered to dietary guidelines post-surgery. Subjective bingeing frequency appeared to be relatively low for all three cases, further declining in frequency at one-year follow-up. At baseline, one participant reported clinically significant depression and anxiety, with no clinically significant depression or anxiety reported at follow-ups in participants that chew and spit. CONCLUSIONS: The current study provides a starting point for the exploration of chew and spit as a pathological symptom of disordered eating in bariatric patients. It highlights the need to further explore chew and spit before and after weight-loss surgery.